FAKTOR-FAKTOR PENYEBAB PUTUS SEKOLAH DARI ANAK PETANI DAN NON-PETANI DI DESA SEA DAN DESA WAREMBUNGAN KECAMATAN PINELENG KABUPATEN MINAHASA - Vinny Briggita Mua; Elsje Pauline Manginsela; Jenny ., Baroleh (Sam Ratulangi University, 2017)
This study aims to determine what factors are the cause of drop out of the children of farmers and non-farmers and whether there are differences in factors that cause drop out of the children of farmers and non-farmers. The analysis used in this research is by using descriptive analysis. This study was conducted from April to June 2017. This study used primary data and secondary data. Primary data was collected by direct interviews based on list of questions that have been prepared to the total respondents as many as 28 respondents. Method of sampling in this research use purposive sampling methods, they are children of farmer and not farmer with their parents. The results of this study indicate that the factors causing drop out of the children of farmers and non-farmers are: internal factors consisting of the will of the child itself and because children do not like school. External factors consisting of the economic condition of parents (unable to finance) and the social environment because affected with children who have dropped out of school first. At the parent level, both farmers and non-farmers, there is no difference in the reasons for dropping out. While at the level of children, both farmers and non-farmers children, there are different reasons for dropping out of school. Non-farmer children are because of internal factors: the willingness of children themselves while the child farmers are because of external factors are because the social environment.*eprm*